Constructing a historical context for Psalm 49 - Spangenberg, Izak J. J. (Old Testament Essays, 2007)
Although the dating of individual psalms has become almost obsolete in scholarly circles, it could be worthwhile to endeavour this for some psalms. Any piece of literature bears fingerprints of the time during which it was created, and this may be of assistance during the process of interpretation. On account of some agreements it is argued that the author of Psalm 49 and the author of the book of Qoheleth were contemporaries. At that stage the upper class in Yehud consisted of two groups : (1) Those who enjoyed their position in society and ignored the social rift between rich and poor; and (2) those who showed solidarity with the poor and attempted to alleviate their plight, even though it sometimes affected their own financial circumstances. The author of Psalm 49 probably belonged to the second group. He wrote his psalm to criticize that section of the upper class who oppressed the poor, and to console those who cared for them.
free